A Study on Stock Returns Based on Liquidity Premium with Empirical Evidence from UK Stock Market - Chen, Hao (2009)
During the past two decades, whether liquidity affect asset pricing has been a hot topic in capital market studies. Theoretically, liquidity is a risk factor that should be priced and is essential in making investment decisions. Plenty of empirical evidence has documented a significant liquidity premium in the US stock market. This paper attempts to examine the cross-section of stock returns based on liquidity premium in the UK stock market during the 1993 to 2008 period of time. Using relative bid-ask spread and turnover ratio as proxies for liquidity, I conduct both cross-sectional and portfolio based time-series regression analyses on around 500 stocks listed on the London Stock Exchange. However, it reports that there is no liquidity premium in the UK stock market. Traditional firm characteristic factors are considered as well. Book-to-market value has been found to influence stock returns, in line with majority literatures. However, the generally accepted size effect cannot be justified.